LATENT HEAT ENERGY STORAGE DEVICE AS А PART OF THE VENTILATION SYSTEM OF INDIVIDUAL HOUSE - Kutnyi, B. A.; Novakh, B. R. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Energy efficient ventilation systems allow to minimize the heat energy consumption for heating supply air, which is very relevant in the context of rising energy prices. It is dealt with the variant of the installation seasonal phase-change heat storage device in the system of ventilation with recuperation of heat energy. Preliminary engineering calculations were perfomed and the quantity of heat storage material (water) necessary for the operation of the ventilation system was determined. The diagrams of change the temperature of the air at the output from the accumulator and distribution of water and ice during the heating period were given. In the article the calculation of seasonal heat storage device on the basis of the water in the supply air ventilation systems are considered , which allows to minimize costs of thermal energy for heating the outside air before it enters to the premises of the house. It is proved that in modern economy conditions development the energy-efficient ventilation system is a promising direction of research and implementations.